Transcranial pulsed electromagnetic fields for treatment-resistant depression: A multicenter 8-week single-arm cohort study: The eighth trial of the Danish University Antidepressant Group. Issue 1 (2020) - Larsen, Erik Roj; Licht, Rasmus W.; Nielsen, René Ernst; Lolk, Annette; Borck, Bille; Sørensen, Claus; Christensen, Ellen Margrethe; Bizik, Gustav; Ravn, Janus; Martiny, Klaus; Vinberg, Maj; Jankuviené, Odeta; et al.
Abstract: Background: The efficacy of antidepressant treatment is fair, but the efficacy is considerably lower in patients failing two or more trials underscoring the need for new treatment options. Our study evaluated the augmenting antidepressant effect of 8-weeks transcranial pulsed electromagnetic field (T-PEMF) therapy in patients with treatment-resistant depression. Methods: A multicenter 8-week single-arm cohort study conducted by the Danish University Antidepressant Group. Results: In total, 58 participants (20 men and 38 women) with a moderate to severe depression as part of a depressive disorder according to ICD-10 who fulfilled criteria for treatment resistance were included, with 19 participants being nonresponders to electroconvulsive therapy during the current depressive episode. Fifty-two participants completed the study period. Scores on the Hamilton Depression Scale 17-items version (HAM-D17 ) decreased significantly from baseline (mean = 20.6, SD 4.0) to endpoint (mean = 12.6, SD 7.1; N = 58). At endpoint, utilizing a Last Observation Carried Forward analysis, 49 and 28% of those participants with, respectively, a nonchronic current episode (≤2 years; N = 33) and a chronic current episode (>2 years; N = 25) were responders, that is, achieved a reduction of 50% or more on the HAM-D17 scale. At endpoint, respectively, 30 and 16% obtained remission, defined as HAM-D17 ≤ 7. On the Hamilton Scale 6-item version (HAM-D6), respectively, 51 and 16% obtained remission, defined as HAM-D6 ≤ 4. Conclusions: The findings indicate a potential beneficial role of T-PEMF therapy as an augmentation treatment to ongoing pharmacotherapy in treatment-resistant depression.